2006
DOI: 10.1097/01.coc.0000197661.09628.03
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Modulated Radiation Therapy (IMRT) Decreases Acute Skin Toxicity for Women Receiving Radiation for Breast Cancer

Abstract: IMRT is associated with a decrease in severity of acute desquamation compared with a matched control group treated with conventional radiation therapy. As with conventional radiation, breast size remains the most important prognostic factor for acute skin toxicity. The CTC grading system for acute radiation dermatitis is not sensitive when applied to modern breast cancer treatment because of its dependence of subjective rating of erythema and inability to gauge variations in desquamation. Further study of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
94
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 19 publications
12
94
1
2
Order By: Relevance
“…IMRT is also effective to increase dose homogeneity and reduce hot spots (11), but even with this technique a 20% to 40% rate of grade 3 acute side effects is observed in the supine position (12,13). The first results of the randomized trial were published in 2013 and showed a 2-to 3-fold reduction in acute skin toxicity with prone IMRT (4).…”
Section: Introductionmentioning
confidence: 99%
“…IMRT is also effective to increase dose homogeneity and reduce hot spots (11), but even with this technique a 20% to 40% rate of grade 3 acute side effects is observed in the supine position (12,13). The first results of the randomized trial were published in 2013 and showed a 2-to 3-fold reduction in acute skin toxicity with prone IMRT (4).…”
Section: Introductionmentioning
confidence: 99%
“…Another study presented the results of a matched‐pair analysis of patients who had received either breast IMRT or standard RT 9. The study reported a significantly lower level of moist desquamation with IMRT than with standard RT using wedge compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of acute dermatitis was found with standard fractionation schedules, 3D-CRT technique compared to IMRT, largest breast size, high BMI, and smoking. 10,[15][16][17] Across these studies there was significant disagreement on the most significant factors for the development of acute breast radiation dermatitis, likely due to the smaller study number of these retrospective reviews. In our study, BMI, total radiation dose, and radiation fractionation schedule appear to be the most important factors for development of breast radiation dermatitis.…”
Section: Discussionmentioning
confidence: 99%